Simulasi dinamik sistem reaktor eksotermal adiabatik dengan alat penukar panas umpan-keluaran (FEHE) - Tri P. Adhi; Gandi R. Setyadi (Jurnal Teknik Kimia Indonesia, 2006)
A study of dinamics behavior on adiahatic exothermal reactor with a Feed-Effluent Heat Exchanger (FEHE) is reported in this paper. In practice of a chemical proces industries, configuration of the heat integration of FEHE system are easi to found at process that involving adiabatic exothermal reactor with the demand of feed's heating and of reactor product's cooling. The FEHE system configuration increase the process thermal efficiency throught the use of heat flow on the reactor product to raise the temperature of reactor feed flow. From the steady state economical point of view, this off cource be very interesting to be implemented, althought controlling and operational considerations are need to be taken into account to keep those advantages un-eliminted by operational and controlling matters. The dynamic simulation can give some illustration on how the hehavior of process operation at FEHE system is. Dynamically this system can be examined so that the boundary of operational parameter which could mantain its stability and trigger unstable system can be known and determined. In this study, the simulation of dynamic and steady state condition on system of FEHE-adiabatic exothermal reactor has been performed by assist of process simulator Aspen-Hysys using ammonia synthesis as the model process. The examined un-stable case were the harmonic osilation phenomena on the operational temperature condition. The objective of this study was to obtain a mathematical correlation model that can be applied in predicting when the un-stable phenomena might be happen.Keywords: FEHE System, Oscillation Temperature, Unstabilize Operation  AbstrakSebuah kajian mengenai kelakuan dinamik sistem reaktor eksothermal adiabatik dengan alat pertukaran panas umpan-keluaran (Feed-Effluent Heat Exchanger, FEHE) disampaikan pada makalah ini. Dalam praktek industri proses kimia, konfigurasi integrasi pwws   sistem  FEHE mudah   ditemukan   pada    proses   yang    melihatkan    reaktor   eksothermal   adiahatik,   dengan kehutuhan pemmw.\·anlfiiiJHIII   reaktor dan pendinginan produk reakt01 Konfigurasi sistem FEHE memherikan  pening/wtan   efisiensi  thermal  proses   melalui  pemanfctatan   a/iran  panas  produk reaktor untuk  menaikkan  tempera fur  a/iran umpan reakt01  Dari sudut pmzdang  ekonomi sistem tunak,   lentu   saja   hal   tersehut   sangat   menarik    1111/uk   diimplemen/asilwn,    a/am   tetapi pertimhangan-pertimhangan    operasi  dan pengendalian   harus  diperhatikan  agar  keuntungan  ini tidak  lere/iminasi  oleh permasalahan-permasalahan   pengendalian   dan pengoperasian.   Simulasi dinamik  dapat  memherilwn  gmnbaran  hagaimana  kelalwan  operasi proses  pada  sistem  FEHE. Secara  dinamik,  sistem  ini dapat  diuji  sehingga  batas-batas  parameter   operasi vang  menjaga kestahilan  danmemicu  ketidakstahilan  dari sis/em  dapat diketaluti  dan ditentukan. Dalam  kajiwz ini simulasi  kondisi  lunak  dan  dinamik. sistem  reaktor  eksothermal  adiahatik-FEHE  dilakukan dengan  hantzwn  simulator  proses  Aspen-Hv.1ys  dengan  mengamhil  sintesi.1·  amoniak  sehagai model  proses.   Kasus  ketidak-stabilan  yang   dikaji  adalah jetwmena    osilasi  harmonik  kondisi tenzperatur operasi.  Tujuan yang  hendak dicapai dari kajian ini adalah untuk mendapatkan  suatu model  korelasi   matematik  yang   dapal  digunalwn   untuk  mcmprediksi  kapan  saat   terjadinyafenomena   ketidak-stahilanlersehut.Kata kunci: Ketidak-stabilan Operasi, Osilasi Temperatur, Sistem FEHE